Fight Hard or Die Trying: Current Status of Lipid Signaling during Plant-Pathogen Interaction - Mehta, Sahil; Chakraborty, Amrita; Roy, Amit; Singh, Indrakant K; Singh, Archana (Plants (Basel, Switzerland), 2021)
Plant diseases pose a substantial threat to food availability, accessibility, and security as they account for economic losses of nearly $300 billion on a global scale. Although various strategies exist to reduce the impact of diseases, they can introduce harmful chemicals to the food chain and have an impact on the environment. Therefore, it is necessary to understand and exploit the plants' immune systems to control the spread of pathogens and enable sustainable agriculture. Recently, growing pieces of evidence suggest a functional myriad of lipids to be involved in providing structural integrity, intracellular and extracellular signal transduction mediators to substantial cross-kingdom cell signaling at the host-pathogen interface. Furthermore, some pathogens recognize or exchange plant lipid-derived signals to identify an appropriate host or development, whereas others activate defense-related gene expression. Typically, the membrane serves as a reservoir of lipids. The set of lipids involved in plant-pathogen interaction includes fatty acids, oxylipins, phospholipids, glycolipids, glycerolipids, sphingolipids, and sterols. Overall, lipid signals influence plant-pathogen interactions at various levels ranging from the communication of virulence factors to the activation and implementation of host plant immune defenses. The current review aims to summarize the progress made in recent years regarding the involvement of lipids in plant-pathogen interaction and their crucial role in signal transduction.
Keywords: pathogens; phosphatidic acid; plants; lipids; oxylipins; microbes